1980
DOI: 10.1029/jb085ib06p03079
|View full text |Cite
|
Sign up to set email alerts
|

Radon anomalies and microearthquakes at Lake Jocassee, South Carolina

Abstract: Continuous low‐level seismic activity was found to occur at Lake Jocassee after the impoundment of the reservoir in 1975. In addition to monitoring seismic activity we began (in January 1976) a series of geochemical measurements in an effort to search for precursors to ML ∼ 2–2.5 events. Discrete water samples were collected from wells and a spring, and their radon content was determined by scintillation counting. These data were comparable to those obtained from a continuous Rn monitor in the spring using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 18 publications
2
15
0
4
Order By: Relevance
“…Recent monitoring programs have typically employed intermittent sampling from natural springs, shallow groundwater wells, or deep (2000m) monitoring wells, and have determined radon concentrations using gas-phase scintillation counting or liquid/liquid extraction of radon and liquid scintillation counting (FRIEDMANN and HERNEGGER, 1978;TALWANI et a/., 1980;TENG, 1980TENG, , 1984WAKITA et a/., 1980aWAKITA et a/., , 1985HAUKSSON, 1981a;HAUKSSON and GODDARD, 1981;ALLEGRI et a/., 1983;CHUNG, 1985;FRIEDMANN, 1985;KING, 1985aKING, , 1986LIV eta/., 1985;SHAPIRO eta/., 1985;SANTOYO et a/., 1987). Continuous monitoring of radon activities is now becoming a more accepted method, as the earlier results have shown that radon anomalies are frequently of short duration.…”
Section: Dissolved Gas Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent monitoring programs have typically employed intermittent sampling from natural springs, shallow groundwater wells, or deep (2000m) monitoring wells, and have determined radon concentrations using gas-phase scintillation counting or liquid/liquid extraction of radon and liquid scintillation counting (FRIEDMANN and HERNEGGER, 1978;TALWANI et a/., 1980;TENG, 1980TENG, , 1984WAKITA et a/., 1980aWAKITA et a/., , 1985HAUKSSON, 1981a;HAUKSSON and GODDARD, 1981;ALLEGRI et a/., 1983;CHUNG, 1985;FRIEDMANN, 1985;KING, 1985aKING, , 1986LIV eta/., 1985;SHAPIRO eta/., 1985;SANTOYO et a/., 1987). Continuous monitoring of radon activities is now becoming a more accepted method, as the earlier results have shown that radon anomalies are frequently of short duration.…”
Section: Dissolved Gas Precursorsmentioning
confidence: 99%
“…The apparent durations of the radon anomalies ranged from a few hours, using the semiconductor detectors (KING, 1985b), to periods of weeks or months (FLEISCHER and MOGRO-CAMPERO, 1985;. Anomaly amplitudes have ranged from an increase of a factor of two above prior backgrounds TALWANI et a/., 1980;STEEL, 1981STEEL, , 1985ABDUVALIYEV eta/., 1984) to increases of factors often or greater (KING, , 1985bMOGRO-CAMPERO et a/., 1980;. In one case (FLEISCHER and MoGRO-CAMPERO, 1985), decreases in radon activity by factors of more than 500 were attributed to seismic effects.…”
Section: Pageophmentioning
confidence: 99%
“…This evidence stimulated research work in this area soon afterwards in many countries. Radon observations, both in soil-gas and in groundwater, revealed many precursory changes in its concentration before an earthquake (Talwani et al 1980;Mogro-Campero et al 1980;Fleischer 1981;Liu et al 1984/85;Virk 1986Virk , 1993Virk , 1997Segovia et al 1989;King et al 1993;Virk and Singh 1992;Igarashi et al 1995;Heinicke et al 1995;Singh et al 1999;Chyi et al 2005;Yang et al 2005). Due to such observed correlation, radon is considered as one of the few promising precursors that can be used for earthquake prediction studies.…”
Section: Introductionmentioning
confidence: 99%
“…have been widely discussed (see e.g. Mogro Campero et al, 1980;Talwani et al, 1980;King, 1980King, , 1985Teng 1980;Hauksson, 1981;Barsukov et al, 1984;Friedmann, 1985). The conclusions which have been drawn, however, are not univocal, but in some cases con tradictory, as they vary with the nature of the precursor (free gas, gas or solid dissolved in water) and of the considered system.…”
Section: Main Features Of Mud Volcanoesmentioning
confidence: 99%